MiR-494-3p regulates mitochondrial biogenesis and thermogenesis through PGC1-α signalling in beige adipocytes. Issue 1 (December 2018) - Lemecha, Mengistu; Morino, Katsutaro; Imamura, Takeshi; Iwasaki, Hirotaka; Ohashi, Natsuko; Ida, Shogo; Sato, Daisuke; Sekine, Osamu; Ugi, Satoshi; Maegawa, Hiroshi
Abstract Mitochondria are critical in heat generation in brown and beige adipocytes. Mitochondrial number and function are regulated in response to external stimuli, such as cold exposure and β3 adrenergic receptor agonist. However, the molecular mechanisms regulating mitochondrial biogenesis during browning, especially by microRNAs, remain unknown. We investigated the role of miR-494-3p in mitochondrial biogenesis during adipogenesis and browning. Intermittent mild cold exposure of mice induced PPARγ coactivator1-α (PGC1-α) and mitochondrial TFAM, PDH, and ANT1/2 expression along with uncoupling protein-1 (Ucp1) in inguinal white adipose tissue (iWAT). miR-494-3p levels were significantly downregulated in iWAT upon cold exposure (p < 0.05). miR-494-3p overexpression substantially reduced PGC1-α expression and its downstream targets TFAM, PDH and MTCO1 in 3T3-L1 white and beige adipocytes (p < 0.05). miR-494-3p inhibition in 3T3-L1 white adipocytes resulted in increased PDH (p < 0.05). PGC1-α, TFAM and Ucp1 mRNA levels were robustly downregulated by miR-494-3p overexpression in 3T3-L1 beige adipocytes, along with strongly decreased oxygen consumption rate. PGC1-α and Ucp1 proteins were downregulated by miR-494-3p in primary beige cells (p < 0.05). Luciferase assays confirmed PGC1-α as a direct gene target of miR-494-3p. Our findings demonstrate that decreased miR-494-3p expression during browning regulates mitochondrial biogenesis and thermogenesis through PGC1-α.